2008
DOI: 10.1021/cm801598k
|View full text |Cite
|
Sign up to set email alerts
|

Site-Isolated Pt-SBA15 Materials from Tris(tert-butoxy)siloxy Complexes of Pt(II) and Pt(IV)

Abstract: Two novel tris(tert-butoxy)siloxy complexes of Pt(II) and Pt(IV) were prepared in high yields, (cod)Pt[OSi(O t Bu)3]2 (1; 87%; cod = 1,5-cyclooctadiene) and Me3Pt(tmeda)[OSi(O t Bu)3] (2; 81%; tmeda = N,N,N′,N′-tetramethylethylenediamine). The structures of these compounds were determined by multinuclear NMR spectroscopy and by single-crystal X-ray analysis. The thermolytic chemistry of 1 and 2 in the solid state was studied by thermogravimetric analysis. The thermal decomposition of these complexes resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 80 publications
6
68
0
Order By: Relevance
“…Mesoporous silicas-MCM-41 and SBA-15-were used as the supports. Previous work has shown that high dispersion of V, 59 Pt, 60 and Ti 61 species can be deposited by using Under inert atmosphere, the moisture-sensitive compounds Ce(O i Pr) 4 and Ce(O t Bu) 4 were dissolved in toluene that had been dried over CaH 2 . These precursors dissolved rapidly at room temperature, yielding a bright yellow solution in the case of Ce(O t Bu) 4 and a honey-colored solution in the case of Ce-(O i Pr) 4 .…”
Section: ' Introductionmentioning
confidence: 99%
“…Mesoporous silicas-MCM-41 and SBA-15-were used as the supports. Previous work has shown that high dispersion of V, 59 Pt, 60 and Ti 61 species can be deposited by using Under inert atmosphere, the moisture-sensitive compounds Ce(O i Pr) 4 and Ce(O t Bu) 4 were dissolved in toluene that had been dried over CaH 2 . These precursors dissolved rapidly at room temperature, yielding a bright yellow solution in the case of Ce(O t Bu) 4 and a honey-colored solution in the case of Ce-(O i Pr) 4 .…”
Section: ' Introductionmentioning
confidence: 99%
“…As such, the Fourier‐transformed magnitude images and un‐transformed images for 6 , 7 , 10 , and 11 are provided in the supplementary information (see the Supporting Information). In general, isolated molecular complexes have previously served as models for the identification of structurally complex species on silica surfaces, so this data should be of use to the zeolite community [20, 29, 97–101] …”
Section: Resultsmentioning
confidence: 99%
“…In general, isolated molecular complexes have previously served as modelsf or the identification of structurally complex specieso ns ilica surfaces, so thisd ata should be of use to the zeolite community. [20,29,[97][98][99][100][101] Reactivity of complexes 10 and 11 with relevancefor Meerwin-Pondorf-Verley transfer hydrogenation over supported group-13m etal catalysts…”
Section: Vibrational Spectroscopic Analysis Of Complexes 6 7 10 11mentioning
confidence: 99%
“…siloxanes or siloxides) in the presence of a silica or alumina support111213141516. Thermolysis of inorganic molecules and clusters has also been shown to yield nanostructured materials1718.…”
mentioning
confidence: 99%
“…Heating to 900 °C resulted in the formation of a black tar-like material, with <30% of total mass remaining, indicating significant compound degradation at this temperature. Previously, Tilley and co-workers have demonstrated that decomposition of single-source precursors (siloxy compounds) can occur at ~150 °C and can efficiently produce homogeneous metal-silica (bulk) materials1215. With this in mind, and considering the thermal profile of compound 1 described above, thermolysis experiments were carried out at 300 °C under a nitrogen atmosphere (see Methods) and the resulting white powder was collected for analysis.…”
mentioning
confidence: 99%